A study on the prevalence of the malaria parasite in the city of Sebha among expatriate workers from neighboring countries. - Al-Haddad , Naima I.; Elsalem , Rugaia M. (Libyan Journal of Science &Technology, 2025)
Libya eliminated malaria in 1973. The majority of malaria cases reported in Libya are imported cases, that travelled abroad, especially to neighboring countries where malaria is endemic. Rapid diagnostic test (RDTs) was conducted to determine the possible risk of malaria among expatriates residing in different areas in Sebha City. The results of this study showed that out of 363 expatriates,141 had an infection with malaria (38.8%). Infection of Plasmodium falciparum and Plasmodium vivax was reported among one hundred one (27.8%) and forty expatriates (11.01%) respectively. The infection rate was higher in males than females, reaching 39.2% and 31.2%, respectively. Infection of malaria was higher among expatriates who came from Chad (55.55%) and Niger (41.35 %). The correlation between the infection rate of malaria and the educational attainment of expatriates was substantially statistically significant (χ2 =9.571; P=0.002). This study confirms that the prevalence of malaria among expatriates is relatively high which may impose a high risk of re-introducing malaria to the southern regions of the country.